2016
DOI: 10.1515/pjap-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Perceived unfairness in teacher-student conflict situations: students’ point of view

Abstract: Student perceptions of injustice in the classroom can evoke destructive behavior, resistance, deception, aggression, and conflict escalation. Our study explores student experiences of unjust teacher behavior in educational settings. Students (N=99) were asked to remember a conflict they experienced during their studies. The conflict descriptions (N=78) were analysed and grouped according the type of perceived injustice (distributive, procedural, interactional) and 22 issues of unfair behaviour (Mikula et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Previous qualitative studies on students' perception of fairness have also demonstrated that students conceptualize fairness related to the classroom elements of teaching, assessment, learning, and classroom interactions (Bempechat et al, 2013;Buttner, 2004;Chory, Horan, & Houser, 2017;Čiuladienė & Račelytė, 2016;Horan et al, 2010;Houston & Bettencourt, 1999;Israelashvili, 1997;Robbins & Jeffords, 2009). These studies reveal that students' overall perception of fairness is shaped by individual contribution and interplay of these dimensions.…”
Section: Insert Figure 1 Herementioning
confidence: 75%
See 2 more Smart Citations
“…Previous qualitative studies on students' perception of fairness have also demonstrated that students conceptualize fairness related to the classroom elements of teaching, assessment, learning, and classroom interactions (Bempechat et al, 2013;Buttner, 2004;Chory, Horan, & Houser, 2017;Čiuladienė & Račelytė, 2016;Horan et al, 2010;Houston & Bettencourt, 1999;Israelashvili, 1997;Robbins & Jeffords, 2009). These studies reveal that students' overall perception of fairness is shaped by individual contribution and interplay of these dimensions.…”
Section: Insert Figure 1 Herementioning
confidence: 75%
“…In addition, research has demonstrated that disrespect through verbal aggression (Claus, Chory, & Malachowski, 2012), insensitive and rude behavior (Bempechat, et al, 2013;Buttner, 2004;Horan et al, 2010), sexual or ethnic humor (Torok, McMorris, & Lin, 2004), sexist, racist, and prejudiced behavior, accusations of students, and implied or stated stupidity (Čiuladienė & Račelytė, 2016;Horan et al, 2010;Israelashvili, 1997) is typically perceived as unfair by students. For example, 71% of Turkish students, in Tomul, Çelik, and Tas (2012) study, reported that their teachers discriminated against them based on their political affiliation, faith, economic background, or ethnicity.…”
Section: Interactional Justicementioning
confidence: 99%
See 1 more Smart Citation
“…CIT is most appropriate when individuals are asked to report retrospectively from memory about salient incidents that happened in the past (Butterfield, Borgen, Amundson, and Maglio, 2005). For this study, CIT serves well to investigate incidents of un/fairness because previous qualitative studies focusing on students' fairness experiences (Alm and Colnerud, 2015;Buttner, 2004;Chory et al, 2017;Čiuladienė and Račelytė, 2016;Horan et al, 2010;Houston and Bettencourt, 1999) demonstrated that un/fairness incidents were particularly salient in students' memories, able to be recalled years later.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to quantitative studies, we identified and reviewed 9 qualitative studies that attempted to develop a conceptualization of social psychology of justice apt for classroom contexts. Israelashvili (1997) interviewed 233 school students in Israel, and Čiuladienė and Račelytė (2016) explored 99 university students in Lithuania to identify experiences of unfairness. These authors reported that their participants experienced unfairness in relation to punishment, abusive and aggressive mistreatment, unbalanced and partial behavior, grading system and examinations, and teacher defensiveness.…”
Section: Social Psychology Of Justice Research In Educationmentioning
confidence: 99%